Banks versus hurricanes: A case study of Puerto Rico after hurricanes Irma and Maria - Peter Anagnostakos; Jason Bram; Benjamin Chan; Natalia Fischl-Lanzoni; Hasan Latif; James M. Mahoney; Donald P. Morgan; Ladd Morgan; Ivelisse Suarez (Federal Reserve Bank of New York, 2023)
We study Puerto Rico's experience after the severe hurricane season of 2017 to better understand how extreme weather disasters affect bank stability and their ability to lend. Despite the devastation wrought by two category 5 hurricanes in a single month, we find relatively modest and transitory impacts on bank performance with no evident decline in lending capacity. We discuss various mitigants that help limit bank exposure to extreme weather and whether these mitigants may be vulnerable given the potential for more severe and more impactful climate events.
Keywords: G21; Q54; 330; climate change; physical risks; hurricanes; banks; Puerto Rico